The positive difference between the areas of two squares is equal to the sum of their perimeters. What is the difference of their perimeters?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a and b be the sides of the BIGGER square and smaller square respectively.
The areas of these squares are a 2 and b 2 respectively while their perimeters measure 4 a and 4 b .
It is given that a 2 − b 2 = 4 a + 4 b .
This is equivalent with :: ( a − b ) ( a + b ) = 4 ( a + b ) Dividing both sides by a + b we get a − b = 4 which, when multiplied by 4
4 ( a − b ) = 4 a − 4 b = 1 6 gives the difference of the perimeters .
Thus, the answer is 1 6 .
a a- b b=(a+b)(a-b)= 4(a+b) Hence (a-b) = 4 Hence 4 (a-b)= 4*4=16 Write a solution.
Let l 1 be the length of the sides for the bigger square and l 2 is for the smaller square.
Therefore: area of big square is l 1 2 and area of small square is l 2 2 , while the perimeter of big square is 4 l 1 and the perimeter of small square is 4 l 2 .
Thus l 1 2 − l 2 2 = 4 l 1 + 4 l 2
so l 1 2 − l 2 2 = 4 ( l 1 + l 2 )
l 1 + l 2 l 1 2 − l 2 2 = 4
l 1 + l 2 ( l 1 + l 2 ) ( l 1 − l 2 ) = 4
l 1 − l 2 = 4 -->(1)
Since we are looking for their difference in perimeters, thus:
= 4 l 1 − 4 l 2
Rearranging that equation we got: = 4 ( l 1 − l 2 )
Substitute with equation (1): = 4 ( 4 )
=16
Let the side length of one square be x , and the side length of the other square be y . Then: ∣ ∣ ∣ x 2 − y 2 ∣ ∣ ∣ = 4 x + 4 y ∣ ∣ ( x + y ) ( x − y ) ∣ ∣ = 4 ( x + y )
As x and y are both positive, we can divide by ( x + y ) : ∣ x − y ∣ = 4 4 ∣ x − y ∣ = 1 6
4 ∣ x − y ∣ is the difference between perimeters 4 x and 4 y .
If two squares, with sides x and y , the difference between the areas would be: x 2 − y 2 This can be rearranged to: ( x + y ) ( x − y )
The second part says that this is equal to the sum of their perimeters. As squares have 4 sides, they're perimeters are 4 x and 4 y . So:
( x + y ) ( x − y ) = 4 x + 4 y
Factorising the right side gives:
( x + y ) ( x − y ) = 4 ( x + y )
Dividing by ( x + y ) gives:
x − y = 4
Now, this is the difference between the edges of the squares, to get the perimeters, we multiply by 4 :
4 x − 4 y = 1 6
Giving us the differences between the perimeters, which equals 1 6
A^2 - B^2 = 4(A+B); (A+B)(A-B) = 4 (A+B); A-B = 4; Now the difference between the two perimeters is 4A-4B I.E 4 (A-B); 4 (A-B) = 16
Problem Loading...
Note Loading...
Set Loading...
∣ a 1 2 − a 2 2 ∣ = 4 ( a 1 + a 2 )
( a 1 + a 2 ) ∣ a 1 − a 2 ∣ = 4 ( a 1 + a 2 )
This implies that ∣ a 1 − a 2 ∣ = 4
and positive difference between perimeters is
4 ∣ a 1 − a 2 ∣ = 4 ∗ 4 = 1 6